Plaatberg on the Caledon Bastaards: hunters, raiders and traders or pious converts of the Wesleyan Missionary Society? - Klatzow, Shelona (Department of Archaeology, 2024)
Plaatberg mission station was established in 1833 by the Wesleyan Missionary Society specifically to minister to a group of people known as Bastaards, under the leadership of Carolus Baatje. As new arrivals in Transorangia who had crossed the boundary from the Cape Colony, the Plaatberg Bastaards came equipped with wagons, horses, guns and ammunition. They showed great skill in adapting to the volatile frontier world in the way that they negotiated the move from colonial farm workers, servants, slaves or disposed Bastaards in the colony to successful traders, raiders and farmers in the Caledon River Valley. Using both written and archaeological evidence, this thesis examines the way that the creolized Plaatberg Bastaards, as inhabitants of the Plaatberg mission station, responded to the Christianising efforts of the Wesleyan Missionaries. The Wesleyans main objective was to transform the Plaatberg Bastaards from “heathen” inhabitants into “civilized” Christian converts, by the imposition of a variety of rules and regulations to achieve this aim. I consider how the very nature of being a creolized mobile group may have influenced the Plaatberg Bastaards responses to the Wesleyan missionaries. These responses may be reflected in the material culture and their use of private and public spaces within the mission as well as in the wider landscape beyond the mission station boundaries. As “heathen” inhabitants of the Wesleyan mission station, the Plaatberg Bastaards had to negotiate their way between and through the aspirations of the missionaries for Christian converts, and the continuity of their own frontier way of life and belief systems. I examine the missionary aspirations for order and control as physically expressed in the public gridlike layout of the mission village itself, being the centre of colonial and religious power. At a finer scale, I address the archaeology of a single domestic precinct and assess the material evidence of dwelling forms, layout and the artefactual mix. At this scale, the order and control desired of the Plaatberg Bastaards by the missionaries was clearly inflected by the layout and utilization of domestic space and hinted at in the use of traded British goods. Additionally, evidence from a rock shelter outside the immediate boundary of the mission, and of hunting, raiding and trading further afield, indicates the private continuity of frontier practice and belief. Selective resistance by the Plaatberg Bastaards to missionary control was strategic and reflected the economic benefits of prior practice, but also the advantages of new practical skills for life within the rapidly changing political landscape of the Northern Cape frontier